Development of TOGA Edu-Tourism with Augmented Reality Technology - Meldayanoor Meldayanoor; Veri Julianto; Muhammad Indra Darmawan; Jupri Mustofa; Firda Adelia (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The development of Edu-tourism based on family medicinal plants (TOGA) in Tirta Jaya Village, supported by Augmented Reality (AR) technology, can enhance education, environmental conservation, and local economic opportunities. This Edu-tourism initiative offers an innovative and sustainable tourism model that positively impacts the tourism sector and the economy.  This study aims to explore and analyze the potential for developing TOGA-based Edu-tourism with AR technology support as an innovative educational tourism model, providing benefits to the community and the environment, while adding value to sustainable local products. This study employs a qualitative descriptive approach with three main stages: a literature review and field data collection to analyze the potential of TOGA and AR technology; an evaluation of TOGA potential based on tourism attraction feasibility, flagship product prioritization, and value-added analysis using the Hayami method; and the development of AR components for interactive education. The results indicate that the combination of TOGA and AR technology can increase public awareness of health, medicinal plant conservation, and local economic empowerment through interactive educational tourism. The educational tourism attraction TOGA Tirta Jaya Village has a high feasibility index, with an average score above 79%, making it worthy of development.   Keywords: Added value; Augmented reality; Edu-tourism; Family medicinal plants (TOGA); TOGA products.